Mean-field modelling of the intermetallic precipitate phases during heat treatment and additive manufacture of Inconel 718 - Anderson, M; Panwisawas, C; Sovani, Y; Turner, R; Brooks, J; Basoalto, H (Elsevier, 2018)
A multi-phase, multi-component mean-field model has been developed for simulating the intermetallic precipitation kinetics in Inconel 718. The aim of this work is to develop predictive capability to aid in process optimisation and explore precipitation kinetics during additive manufacturing (AM). The model has been calibrated to available experimental data, and then applied to predict precipitation kinetics during typical solid solution treatment and aging operations, and during AM. It is shown that a Computer Coupling of Phase Diagrams and Thermochemistry (CALPHAD) based modelling approach provides a unified particle growth rate which can capture the growth, coarsening and dissolution of , and δ precipitates under relevant heat treatment conditions. To apply the model to AM, finite element simulations of a simple rectangular build have been carried out, using a property switching method to simulate the material deposition. The component level simulation provides the thermal fields to calculate precipitation kinetics during deposition, also allowing for the examination of the heat affected zone in the substrate. The modelling approach can capture the repeated nucleation and dissolution of precipitates that occurs during AM. The model shows good agreement with experimental data when applied to predicting precipitation kinetics during heat treatment.